Implementasi Metode Human Centered Design dalam Perancangan Interior Senior Entertainment Center di Mall di Surabaya - Pranoto, Tania; Thamrin, Diana; Pradjonggo, Celline Junica (Intra, 2019)
Mall is one of the most accessible recreational places for all because of the variety of entertainment options. However, the lack of facilities that are accessible to the elderly plus their weak physical conditions caused the limitation of activities that they can do in the mall. The interior design of senior entertainment center in the mall in Surabaya can be an alternative option for recreational, educational, and socialization activity between elders. The design method used is Stanford School thinking of design method that has been developed. The method consists understand, observe, resolving needs, prototype, test, story telling, and business model. The design raised the Old but Gold concept which provides facilities to accommodate seniors’ activities, such as activity space, games, and exercise rooms with the aim of increasing happiness, socialization, and support good health both in body as well as their spirit.